SPERM LONGEVITY AND RECOVERY RATE OF BELGIAN BLUE CATTLE IN DIFFERENT EXTENDER - Andi Murni Nurul Maulidyah; Muhammad Agil; Syahruddin Said; Taufiq Purna Nugraha; Raden Iis Arifiantini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Frozen semen from Belgian Blue cattle is in high demand among farmers, as evidenced by the increasing interest in this breed's semen. However, the freezing process reduces sperm motility and viability. This study aimed to assess the viability of sperm post-freezing and the sperm recovery rate (RR) in Belgian Blue cattle using different extenders. Semen was collected, evaluated, and diluted in four extenders: three commercially available ones—BoviFree®, AndroMed®,, and Steridyl®,—and a homemade extender, Tris Egg Yolk (TEY). Longevity and RR tests were conducted 24 h after freezing. Progressive motility was assessed using a portable computer-assisted sperm analysis (CASA) device (Androscope Minitube, Germany). The results indicated that sperm motility was higher in the BoviFree®, and AndroMed®, extenders after 3 h compared to the other extenders (p <0.05). After 4 h, motility remained higher in the BoviFree®, extender than in TEY. The RR values showed no significant differences among the extenders (p< 0.05). The study concluded that sperm longevity in Belgian Blue cattle was optimal in the BoviFree®, extender, with consistently good sperm RR values across all extenders.